“Menstruation is a Fearful Thing”: A Qualitative Exploration of Menstrual Experiences and Sources of Information About Menstruation Among Adolescent Schoolgirls - Betsu BD; Medhanyie AA; Gebrehiwet TG; Wall LL (Dove Medical Press, 2023)
Balem Demtsu Betsu,1 Araya Abrha Medhanyie,2 Tesfay Gebregzabher Gebrehiwet,3 L Lewis Wall3- 5 1Department of Midwifery, College of Health Sciences, Mekelle University, Mekelle, Ethiopia; 2School of Public Health, College of Health Sciences, Mekelle University, Mekelle, Ethiopia; 3Department of Anthropology, College of Arts and Sciences, Washington University in St. Louis, Campus, St. Louis, MO, USA; 4Department of Obstetrics & Gynecology, Washington University in St. Louis, St. Louis, MO, USA; 5Department of Obstetrics & Gynecology, Ayder Comprehensive Specialized Hospital, College of Health Sciences, Mekelle University, Mekelle, EthiopiaCorrespondence: Balem Demtsu Betsu, Email balemdim@gmail.comBackground: Although menstruation is a biological phenomenon, it is still subjected to secrecy, shame, and negativity. Schoolgirls lack access to appropriate sources of information about menstruation. Little is known about the content of the information provided to schoolgirls concerning menstruation in northern Ethiopia. This study explored schoolgirls' experiences and the content of information they receive concerning menstrual hygiene management in Tigray.Methods: A qualitative design was implemented. Focus group discussions and in-depth interviews were conducted using the local language among 79 schoolgirls who had experienced menarche. Data were audio-recorded, transcribed, translated, and imported into ATLAS.ti-7.5.18 computer software for analysis. Data were coded and analyzed using a thematic analysis.Results: Five themes have emerged from the analysis: 1) there is an indistinct and haphazard source of menstrual information; 2) menstruation is perceived as "a natural gift"; 3) menstruation is also considered fearful and embarrassing; 4) negative community perceptions of menstruation lead to menstrual restrictions, and 5) lack of privacy for dealing with menstrual issues as well as the scarcity of menstrual hygiene management materials is an on going problem. Schoolgirls have indistinct and haphazard sources of information concerning menstrual hygiene management, obtaining it from teachers, mothers, sisters, and friends, but the information they receive is shrouded in secrecy and often is factually incorrect. Menstruation is commonly linked to notions of sexuality, shame, and the approach of marriageability.Conclusion: The information that schoolgirls in rural Tigray receive about menstrual hygiene management is inaccurate, insufficient, and encumbered with social taboos. Thus, schoolgirls do not have an adequate understanding of the physiology of menstruation and do not receive adequate emotional support at menarche, leaving them with feelings of embarrassment and anxiety. There should be efforts to implement programs that change community perceptions about menstruation.Keywords: menstruation, menstrual hygiene management, adolescent schoolgirls, information, northern Ethiopia